Tindak Pidana Pencucian Uang (Money Laundering) di Indonesia - Dharyanto, Ikang (LAW REVIEW, 2004)
Money laundering is the use of money derived from illegal activity by concealing the identity of the individuals who obtained the money and converting it to assets that appear to have come from a legitimate source. It can simplify things by saying that money laundering is a process to make dirty money appear to be clean. The appearance part is very important, because under American Law, dirty money is never "clean", no matter Â how many times it goes through the rinse and spin cycle.Â